Review of technology for normally-off HEMTs with p-GaN gate. (May 2018) - Greco, Giuseppe; Iucolano, Ferdinando; Roccaforte, Fabrizio
Abstract: Owing to the high carrier density and high electron mobility of the two dimensional electron gas (2DEG), high electron mobility transistors (HEMTs) based on gallium nitride (GaN) are suitable devices for high power and high frequency applications. Clearly, the presence of the 2DEG at the interface of AlGaN/GaN heterostructures makes HEMTs intrinsically normally-on devices. However, for power electronics applications, normally-off operation is desired for safety reasons and to simplify the driver circuitry. In this context, although several approaches to obtain normally-off transistors have been reported in the literature, normally-off GaN-based HEMTs with a p-GaN gate is among the most promising and the only commercially available today. This paper reviews the most relevant technological issues for normally-off HEMTs with a p-GaN gate. First the operation principle and the impact of the heterostructure parameters are discussed. Then, the possible effects of the dry etching process of p-GaN are shortly mentioned. Thereafter, the role of the metal/p-GaN interface and the impact of the thermal processes on the electrical characteristics are widely discussed. Finally, recent alternative approaches proposed to avoid the use of the p-GaN dry etching are presented.